Different factors considered in project selection at public and private R&D institutes - Lee, Mushin; Om, Kiyong
With respect to the factors considered in the selection process of an R&D project from multiple proposals, are the factors that are considered important at public R&D institutes significantly different from those at private ones? To answer this question, we tried a questionnaire survey approach. This paper is written to report the results. It is found that, in selecting a development project, the key factors considered important at public R&D institutes differ from those at private ones. That is, the market characteristics factor is considered more important at private R&D institutes, while the diffusion effect factor is considered more important at public institutes. In selecting a research project, and also with respect to other factors in selecting a development project, no significant difference is found. Though the generalizabilityof the findings is evidently limited, we believe that the results are meaningful to the students of R&D management.
The writers look at the selection of projects in public and private R&D institues and use a questionnaire survey of researchers in private and public Korean R&D institutes to obtain data and draw conclusions
Keywords: Project selection; R&D institutes